SOSIO-EKONOMI SEBAGAI FAKTOR NON-PERFORMING FINANCING PADA LEMBAGA KEUANGAN MIKRO SYARIAH - Barianto Nurasri Sudarmawan (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The study analyzes the factors that affect Non-Performing Financing (NPF) using the customer's socio-economic indicators (age, gender, education level, county). The research chose Indonesia as the object of research, because it has the largest Muslim population in the world and the development of Sharia Microfinance Institutions (MFIs) in this country is quite promising. To identify the factors that influence non-performing financing in Islamic MFIs, we use the logit model to estimate the probability of factors affecting NPF. The results of this study indicate that the socio-economic factors of the customer, namely age, gender, education level, influence problematic financing. The results of this study give a framework for making strategic policy to maintain Sharia MFIs stability based on the dimensions of age, gender, level and education.